Prebiotic food intake and biochemical measures in diabetic patients: A cross-sectional study from the Sabzevar Persian Cohort - Rahil Mahmoudi; Maral Nabaee; Akram Kooshki; Saba Shourideh Yazdi; Mahboubeh Neamatshahi; Elaheh Foroumandi (PLoS ONE, 2025)
Background With the high prevalence of diabetes worldwide and the known benefits of functional foods in controlling diabetes, this study aimed to explore the connection between prebiotic food intake and biochemical indices in diabetic patients. Methods This cross-sectional study was conducted on 504 participants with type 2 diabetes who were part of the Sabzevar Persian Cohort study that was initiated in February 2018. A 148-items food frequency questionnaire was utilized to assess the daily amount of prebiotic food consumption. Blood serum samples were collected from participants to measure fasting blood sugar levels, lipid profile, and kidney function indicators. Additionally, anthropometric measurements were taken following standard protocols. Statistical analyses were performed using SPSS version 20, with correlation tests adjusted for confounders, and significance set at p < 0.05. Results This study involved 44.9% male and 55.1% female participants, with an average age of 54.81 ± 7.65 years. A significant correlation was observed between soybean consumption and serum low density lipoprotein (LDL) status (R = −0.110, P = 0.014). Moreover, a higher intake of banana was linked to lower blood urea nitrogen (BUN) levels (R = −0.109, P = 0.015). Furthermore, the consumption of honey exhibited a negative association with both systolic blood pressure (BP) (R = −0.106, P = 0.018) and diastolic BP (R = −0.132, P = 0.003). Green peas intake was also inversely associated with DBP (R = −0.092, P = 0.039). Conclusion This study found a positive correlation between the regular intake of prebiotic foods and improved management of BUN, LDL, and BP in individuals with type 2 diabetes. However, further mechanistic studies are necessary to better understand the potential causal effects of prebiotic foods on metabolic health in this population.